Implementasi Metode Importance Performance Analysis (IPA) Untuk Pengukuran Indeks Kepuasan Masyarakat (IKM) Terhadap Pelayanan Administrasi di Desa Klatakan - Asror, Moh. Miftahul; Rosyidah, Ulya Anisatur; Daryanto, Daryanto (Puslitbang Akademi Relawan TIK Indonesia, 2024)
Klatakan village of Kendit district in Situbondo district is one of the villages that strives to improve the performance of public services to the community. We need an information system that can measure and manage the value of the Public Satisfaction Index (IKM) from the questionnaire filled in by the public through the website and performed satisfaction calculations with the method of Importance Performance Analysis (IPA). The results of data processing and analysis using this web-based information system, the public satisfaction index to the services of the Klatakan Village Office is 80,43% with three variables not matching. From the results of Quadrant 1 there are some things that are expected to be described as priority services, Quadrants 2 show achievements or services that can be sustained, Quadran 3 is input from the community related to services with low priority so it needs to be improved and Quadrans 4 is the opinion of the public about what services are considered excessive from the Klatakan village device to the community